A series of 18F-labelled pyridinylphenyl amides as subtype-selective radioligands for the dopamine D3 receptor - Hocke, Carsten; Maschauer, Simone; Hübner, Harald; Löber, Stefan; Utz, Wolfgang; Kuwert, Torsten; Gmeiner, Peter; Prante, Olaf (ChemMedChem, 2010)

CoMFA and CoMSIA Investigations of Dopamine D3 Receptor Ligands Leading to the Prediction, Synthesis and Evaluation of Rigidized FAUC 365 Analogues - Hübner, Harald; Gmeiner, Peter; Utz, Wolfgang; et al. (Bioorganic & Medicinal Chemistry, 2006)
Taking advantage of our in-house experimental data on dopamine D3 receptor modulators, we have successfully established highly significant CoMFA and CoMSIA models (qcv2 = 0.82 / 0.76). These models were carefully investigated to assure their stability and predictivity (rpred2 = 0.65 / 0.61) and subsequently applied to guide experimental investigations on the synthesis and receptor binding of three conformationally restricted D3 ligands. Besides the high D3 affinity, the test compound 45, incorporating a trans-1,4-cyclohexylene partial structure, exhibited improved (∼3200-fold) selectivity over the D4 subtype. © 2006 Elsevier Ltd. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2006.nat.dchph.lphch.comfaa
Keywords: 3D-QSAR; CoMFA/CoMSIA model; Dopamine D3 Receptor; Phenylpiperazine

CoMFA and CoMSIA Investigations Revealing Novel Insights into the Binding Modes of Dopamine D3 Receptor Agonists - Hübner, Harald; Gmeiner, Peter; Utz, Wolfgang; et al. (Journal of Medicinal Chemistry, 2005)
As an extension of a series of dopamine D3 receptor agonists involving FAUC 54, ex-chiral pool synthesis, and biological evaluation of 3-substituted 7-aminotetrahydroindolizines was performed. Considering the structural features of both series of enantiomers, we developed a novel alignment hypothesis for D3 agonists, allowing for the placement of the aromatic moieties on two alternative, adjacent positions. CoMFA and CoMSIA analyses yielded significant cross-validated q2 values of 0.726 and 0.590, respectively, when a newly invented program application (IRAS) controlling the alignment selection proved to be useful. Employing the CoMFA/CoMSIA contribution maps, we were able to transform a previously constructed homology model of the D3 receptor from an inactive into an activate state. Besides the established ionic interactions, we propose π-stacking with Phe6.51 and a hydrogen bond between His6.55 and the acyl moiety to be primarily involved in the D3 receptor binding of FAUC 54 and its analogues. © 2005 American Chemical Society.
UnivIS-Import:2015-03-09:Pub.2005.nat.dchph.lphch.comfaa

Comparative molecular field analysis of dopamine D4 receptor antagonists including 3-[4-(4-chlorophenyl)piperazin-1-ylmethyl]pyrazolo[1,5-a]pyridine (FAUC 113), 3-[4-(4-chlorophenyl)piperazin-1-ylmethyl]-1H-pyrrolo-[2,3-b]pyridine (L-745,870), and clozapine. - Lanig, Harald; Utz, Wolfgang; Gmeiner, Peter (Journal of Medicinal Chemistry, 2001)
A CoMFA study was undertaken to elucidate the correlation of biological activity and structural parameters of 25 dopamine D4 antagonists. A special point of interest is that we have included the atypical D4 antagonist clozapine as a structural template for all other compounds. After comparing potential protonation sites at semiempirical (AM1) and ab initio (6-31G(d)) levels of theory, possible conformations of the lead compound 3-[4-(4-chlorophenyl)piperazin-1-ylmethyl]pyrazolo[1,5-a]pyridine (FAUC 113) were investigated by systematic semiempirical conformational analysis. The final conformation of FAUC 113, which was used as a template for the other compounds in the dataset, was chosen by clustering and rigid body alignment of all conformations to clozapine. The CoMFA applied on the final alignment resulted in a q2cv of 0.739. To elucidate the influence of the absolute orientation of the molecules within the grid space, the entire dataset was systematically rotated (1296 steps) within the lattice. The Gaussian-shaped distribution of the q2cv values spanned the range of 0.699-0.794 and therefore supports the significance of the analysis.

Comparative Molecular Field Analysis of Dopamine D4 Receptor Antagonists Including 3-[4-(4-Chlorophenyl)piperazin-1-ylmethyl]pyrazolo[1,5-a]pyridine (FAUC 113), 3-[4-(4-Chlorophenyl)piperazin-1-ylmethyl]-1H-pyrrolo[2,3-b]pyridine (L-745,870), and Clozapine - Lanig, Harald; Utz, Wolfgang; Gmeiner, Peter; Lanig, Harald (Journal of Medicinal Chemistry, 2001)
UnivIS-Import:2015-03-09:Pub.2001.nat.dchph.lphch.compar

Conjugated Enynes as Nonaromatic Catechol Bioisosteres: Synthesis, Binding Experiments and Computational Studies of Novel Dopamine Receptor Agonists Recognizing Preferentially the D3 Subtype - Utz, Wolfgang; Gmeiner, Peter; Hübner, Harald; et al. (Journal of Medicinal Chemistry, 2000)
To evaluate nonaromatic catechol bioisosteres, the conformationally restrained enynes I and enediynes 2 were synthesized via palladium-catalyzed coupling as the key reaction step. Subsequent receptor binding studies at the dopamine receptor subtypes D1, D(2 long), D(2 short), D3, and D4 showed highly interesting binding profiles for the enynes 1a and lb when compared to dopamine. At the guanine nucleotide-sensitive high-affinity binding site of the D3 receptor, the target compound 1b (K(i) = 5.2 nM) was 10-fold more potent than dopamine but less potent at the D2 and D4 subtypes. In contrast to dopamine the agonists 1a and lb showed strong selectivity for the receptors of the D2 family (D2-D4). As far as we know, this study represents the first report on nonaromatic dopamine agonists. Comparison of molecular electrostatic potentials, derived from semiempirical molecular orbital calculations, and lipophilicity maps was performed.
UnivIS-Import:2015-03-06:Pub.2000.nat.dchph.lphch.conjug

Influence of nonenzymatic posttranslational modifications on constitution, oligomerization and receptor binding of S100A12 - Augner, Kerstin; Eichler, Jutta; Utz, Wolfgang; Pischetsrieder, Monika (PLoS ONE, 2014)
This study examined the effect of methylglyoxal (MGO)-derived nonenzymatic posttranslational modifications (nePTMs) on the binding affinity of S100A12 to its natural receptor for advanced glycation end-products (RAGE). Binding of MGOmodified S100A12 to RAGE decreased significantly with increasing MGO concentration and incubation time. Ca2+-induced S100A12 hexamerization was impaired only at higher MGO concentrations indicating that the loss of affinity is not predominantly caused by disturbance of ligand oligomerization. nePTM mapping showed carboxyethylation of lysine (CEL) and the N-terminus without preferential modification sites. Besides, hydroimidazolone, hemiaminals, argpyrimidine, and tetrahydropyrimidine rapidly formed at R21. Even at the highest modification rate, hexamerization of synthesized CEL-S100A12 was unaffected and RAGE-binding only slightly impaired. Thus, nePTMs at R21 seem to be the major cause of MGOinduced impairment of S100A12 oligomerization and RAGE binding.
UnivIS-Import:2015-03-09:Pub.2014.nat.dchph.llmch.influe

Lignans and neolignans from Krameria parvifolia - Achenbach, Hans; Utz, Wolfgang; Lozano, Blanca; Guajardo Touché, Elsa M.; Moreno, Sergio (Phytochemistry, 1996)
From the roots of Krameria parvifolia, the new neoolignans (2R,3R,2'R)- 2,3-dihydro 2 (4-hydroxy-phenyl)-5-(2'-hydroxypropyl)-3-methylbenzofuran and 2 (4,6 dihydroxy-2-methoxyphenyl) 5 (3 hydroxy-propyl)benzotoran were isolated. In addition, conocarpan, eupomatenoid 6, hermosillol, ratanhiaphenol I, ratanhiaphenol III. zapotecol, caffeoylcycloartenol and a further 10 known compounds, all belonging to the lignans, neolignans and norneolignans, respectively, were characterized.
UnivIS-Import:2015-03-05:Pub.1996.nat.dchph.lphch.lignan
Keywords: Krameria parvifolia; Krameriaceae; lignans; neolignans; nor-neolignans

Neolignans, nor-neolignans and other compounds from roots of Krameria grayi - Achenbach, Hans; Utz, Wolfgang; Sanchez, H.V.; Guajardo Touché, Elsa M.; Verde, Julia; Dominguez, Xorge A. (Phytochemistry, 1995)
From the roots of Krameria grayi, a new nor-neolignan was isolated, besides 14 known lignan-type and three cycloartane-type compounds. © 1995.
UnivIS-Import:2015-03-05:Pub.1995.nat.dchph.lphch.neolig
Keywords: 2-(4-methoxyphenyl)-5-((E)-1-propenyl)benzofuran; Krameria grayi; Krameriaceae; neolignans; nor-neolignans; roots

Rationally Based Efficacy Tuning of Selective Dopamine D4 Receptor Ligands Leading to the Complete Antagonist 2-[4-(4-Chlorophenyl)piperazin-1-ylmethyl]pyrazolo[1,5-a]pyridine (FAUC 213) - Utz, Wolfgang; Löber, Stefan; Gmeiner, Peter; Hübner, Harald (Journal of Medicinal Chemistry, 2001)
UnivIS-Import:2015-03-09:Pub.2001.nat.dchph.lphch.ration_6

Regioselective analysis of heat-induced conformational changes of β-lactoglobulin by quantitative liquid chromatography–mass spectrometry analysis of chemical labeling kinetics - Liu, Jiajia; Gensberger-Reigl, Sabrina; Zenker, Hannah; Schichtl, Theresa Maria; Utz, Wolfgang; Pischetsrieder, Monika (Food Chemistry, 2024)
β-Lactoglobulin is a main allergen in cow's milk; its allergenicity is strongly impacted by processing. To understand heat-induced epitope-specific effects, the present study analyzed regiospecific conformational changes of heated native β-lactoglobulin variant A (BLG-A). Complementary fluorescence spectroscopy methods indicated two denaturation phases comprising minor sequential conformational changes (25–75 °C) and complete transitions (80–90 °C). Regioselective conformational changes of BLG-A in the native state (25 °C), sequential (70 °C) and complete transition (90 °C) were determined by quantitative liquid chromatography–mass spectrometry analysis of chemical labeling kinetics covering 14 lysine residues and the N-terminus. Conformational changes in two phases were observed for N-terminus, K8 (both N-terminal chain), K60 (β-sheet C), K75 (β-sheet D), K77 (DE loop), K83 (β-sheet E), K100 and K101 (FG loop). The residues K14 (β-sheet A1), K47 (β-sheet B), K69, K70 (both β-sheet D), and K91 (β-sheet F) were not involved in conformational changes.
CRIS-Team Scopus Importer:2024-08-09
Keywords: Allergenic epitopes; Chemical labeling kinetics; Conformational changes; Heat-processing; Quantitative liquid chromatography–mass spectrometry analysis; β-Lactoglobulin

Structure-Selectivity Investigations of D2-like Receptor Ligands by CoMFA and CoMSIA Guiding the Discovery of D3 Selective PET Radioligands - Utz, Wolfgang; Prante, Olaf; Hübner, Harald; Kuwert, Torsten; Gmeiner, Peter; et al. (Journal of Medicinal Chemistry, 2007)
Elucidation of the physiological role of the D3 receptor and its distribution in the brain using positron emission tomography (PET) is hampered by the lack of bioavailable subtype selective tracer ligands. To develop appropriate D3 radioligands, we designed an integrative procedure involving the elucidation of structural features determining D3 selectivity over both congeners D2 and D4 by comparative molecular analysis. Thus, we have successfully generated CoMFA and CoMSIA models based on the affinitiy differences of a series of 79 ligands representing a broad range of selectivities. These models yielded highly significant cross-validations (q2 cv(D3/D2) = 0.86; q2 cv(D3/D4) = 0.92) and excellent predictions of a 16-ligand test set (r2 pred = 0.79-0.93). Exploiting this information, synthesis and receptor binding studies directed us to the fluorinated lead compounds 78 and 79, featuring subnanomolar D3 affinities and considerable selectivities over D2 and D4 and, subsequently, to the subtype selective PET tracers [ 18F]78 and [18F]79. © 2007 American Chemical Society.
UnivIS-Import:2015-04-14:Pub.2007.nat.dchph.lphch.struct

Studies on Krameriaceae. Part 6. Lignans and nor-neolignans from Krameria interior - Dominguez, Xorge A.; Sanchez, H.V.; Espinoza, Griselda C. B.; Verde, Julia S.; Achenbach, Hans; Utz, Wolfgang (Phytochemistry, 1990)
UnivIS-Import:2015-03-05:Pub.1990.nat.dchph.lphch.studie

Studies on Krameriaceae. Part 7. Lignans from Krameria ixina - Achenbach, Hans; Utz, Wolfgang; Usubillaga, Alfredo; Rodriguez, Henry A. (Phytochemistry, 1991)
UnivIS-Import:2015-03-05:Pub.1991.nat.dchph.lphch.studie

Studies on Krameriaceae. Part 8. Neolignans, norneolignans, and other compounds from Krameria sonorae - Dominguez, Xorge A.; Espinoza, Griselda C. B.; Rombold, C.; Utz, Wolfgang; Achenbach, Hans (Planta Medica, 1992)
UnivIS-Import:2015-03-05:Pub.1992.nat.dchph.lphch.studie

Studies on Krameriaceae. Part 9. Neolignans and nor-neolignans from Krameria paucifolia - Achenbach, Hans; Utz, Wolfgang; Dominguez, Xorge A. (Phytochemistry, 1993)
UnivIS-Import:2015-03-05:Pub.1993.nat.dchph.lphch.studie